Farmakoterapi nyeri neuropatik - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
The most important clinical development in chronic pain during the past decade has not been new treatments but a thoroughly revised interpretation of the mechanisms that act to maintain pain. Pain is no more seen as a predetermined result of simple activation of certain natural structures. It is now understood to be dynamic phenomenon due to myriad pathophysidogical changes in the peripheral and central nervous system is response to disease, injury, or loss of function. Various mechanisms have been proposed to account for the paradoxical appearance of following injury or dysfunction of the peripheral or central nervous system. Central pain produced by lessions of the central nervous system (CNS), however , not all CNS lessions produce a central pain syndrome. Lessions can occur in the spinal cord, brainstem, and brain . Most cases of central pain are associated with spinal cord lessions. Pain may be produced by many different types of lines of the peripheral nervous system. Peripheral nerve pain may occur because of reflex sympathetic dystrophy or causalgia, herpes zorter, polyneuropathy, radiculopathy, plexopathy, and multiple entrapment neuropathies. In the past, neuropathic pain patients have suffered from less than optimal treatment approaches determind by their primary illness. It has become clear that there is a need to modify therapeutic strategies. This paper has outlined a rational mechanism sign and symptom-based approach to the evaluation and treatment of patients with neuropathic pain. It is important to point out that this approach is still envolving. Pharmacotherapy includes tricyclic antidepressants, narcotics, anticonvulsants, and antiarrhythmics.